Stirling Number of the Second Kind of Number with Greater/Proof 2

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $n, k \in \Z_{\ge 0}$ such that $k > n$.


Let $\displaystyle {n \brace k}$ denote a Stirling number of the second kind.

Then:

$\displaystyle {n \brace k} = 0$


Proof

The proof proceeds by induction.

For all $n \in \N_{> 0}$, let $\map P n$ be the proposition:

$\displaystyle k > n \implies {n \brace k} = 0$


Basis for the Induction

$\map P 0$ is the case:

$\displaystyle {0 \brace k} = \delta_{0 k}$

from Stirling Number of the Second Kind of 0.


So by definition of Kronecker delta:

$\forall k \in \Z_{\ge 0}: k > 0 \implies \displaystyle {0 \brace k} = 0$

and so $\map P 0$ is seen to hold.


This is the basis for the induction.


Induction Hypothesis

Now it needs to be shown that, if $\map P r$ is true, where $0 \le r$, then it logically follows that $\map P {r + 1}$ is true.


So this is the induction hypothesis:

$\displaystyle k > r \implies {r \brace k} = 0$


from which it is to be shown that:

$\displaystyle k > r + 1 \implies {r + 1 \brace k} = 0$


Induction Step

This is the induction step:


\(\displaystyle {r + 1 \brace k}\) \(=\) \(\displaystyle k {r \brace k} + {r \brace k - 1}\)
\(\displaystyle \) \(=\) \(\displaystyle r \times 0 + {r \brace k - 1}\) Induction Hypothesis
\(\displaystyle \) \(=\) \(\displaystyle r \times 0 + 0\) Induction Hypothesis: $k > r + 1 \implies k - 1 > r$
\(\displaystyle \) \(=\) \(\displaystyle 0\)

So $\map P r \implies \map P {r + 1}$ and the result follows by the Principle of Mathematical Induction.


Therefore:

$\displaystyle \forall n \in \Z_{\ge 0}: k > n \implies {n \brace k} = 0$

$\blacksquare$